Embedding Ethical Impact Assessment in Nanosafety Decision Support. Issue 36 (23rd July 2020) - Malsch, Ineke; Isigonis, Panagiotis; Dusinska, Maria; Bouman, Evert A.
Abstract: Nanotechnology is a key enabling technology, which is developing fast and influences many aspects of life. Nanomaterials are already included in a broad range of products and industrial sectors. Nanosafety issues are still a matter of concern for policy makers and stakeholders, but currently, there is no platform where all stakeholders can meet and discuss these issues. A comprehensive overview of all the issues in one single dashboard presenting the output of a decision support system is also lacking. This article outlines a strategy for developing one innovative part of a modular decision support system, designed to support the work of a new Risk Governance Council (RGC) for nanomaterials which will be established through the combined efforts of the GOV4NANO, NANORIGO, and RiskGONE H2020 projects. This new module will consist of guidelines for Ethical Impact Assessment (EIA) for nanomaterials and nanoenabled products. This article offers recommendations for adapting the European Committee for Standardization (CEN) prestandard on Ethical Impact Assessment CWA (CEN Workshop Agreement) 17145‐2:2017 (E), to fit into the more‐encompassing decision support system for risk governance of nanomaterials within the RiskGONE project. Abstract : A strategy is presented for developing one innovative part, incorporating ethical aspects, in a modular decision support system. The system is designed to support the work of a new Risk Governance Council for nanomaterials. The new module will consist of guidelines for ethical impact assessment for nanomaterials and nanoenabled products.